علاقة المسؤولية الاجتماعية بالرضا الوظيفي - عون, محمد الصالح; بوراس, نرجس (جامعة الوادي university of Eloued, 2016)
Abstract: We have addressed in our study the relationship of corporate social responsibility and job satisfaction in the valley at the University Professors Faculty of Social and Human Sciences in the university of eloued. A descriptive study Analytical aimed to find out the relationship and analyzed between social responsibility and job satisfaction among the professors of the Faculty of Social and Human Sciences, where follow researchers descriptive and analytical approach by choosing a survey sample in the institution under study, where we used a questionnaire and observation tools to collect data, and then worked to prove hypotheses using The program spss, and the study concluded that there is a relationship between social responsibility and job satisfaction among faculty members, and that most of the respondents are dissatisfied with functionally and see that the administration is committed to their social responsibilities
دراسة حالة كلية العلوم الانسانية والاجتماعية بجامعة الوادي
مذكرة ماستر علم اجتماع تخصص تنظيم وعمل
Keywords: المسؤولية الاجتماعية، الرضا الوظيفي; Responsabilité sociale, satisfaction au travail; Social responsibility, job satisfaction